The relationship between organizational creativity and demographic characteristics with the productivity of organizational tasks - Keshtkar, Sara; Javanmardi, Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: Achieving sustainable productivity, creativity, innovation, and quality of life depends on efficient, effective, intelligent, committed management and human resources. Therefore, the purpose of this research was to investigate the relationship between organizational creativity and demographic characteristics with the productivity of the organizational tasks of the employees of the General Department of Education of Fars province. Methodology: The current research design is a correlational descriptive one. This research’s statistical population was comprised of all the employees of the Education Department of Fars province, whose number is 450 (67 women and 383 men). Among them, 205 people were tested based on Morgan’s table and by multi-stage cluster sampling method as the selected sample group using two questionnaires of organizational creativity of Rendsip and a questionnaire of human force productivity. The data were analyzed using descriptive statistics and statistical correlation tests using SPSS21 software. Results: The obtained results showed no significant difference between the average organizational creativity and the productivity of organizational tasks of both sexes, but there is a significant difference between the average organizational creativity and the productivity of organizational tasks according to age, education, and work experience. Conclusion: creativity and fostering the creative process of problem-solving and paying attention to the innovations of people in the organization can increase the quality of employees in organizations.